2004
DOI: 10.1242/jeb.00845
|View full text |Cite
|
Sign up to set email alerts
|

The early ontogeny of neuronal nitric oxide synthase systems in the zebrafish

Abstract: nNOS mRNA expression started at 20·h.p.f. and ended at 55·h.p.f. Between 40 and 55·h.p.f., nNOS mRNA expression started in peripheral organs, forming distinct populations after hatching within or in the vicinity of the presumptive swim bladder, enteric ganglia, and along the alimentary tract and nephritic ducts. Expression of nNOS mRNA correlated with the neuronal differentiation pattern and with the timing and degree of cGMP production.These studies indicate spatio-temporal actions by NO during embryogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 76 publications
(121 reference statements)
8
36
0
Order By: Relevance
“…and the expression of nitric oxide synthase (NOS), indicative of nitrergic neurons, as well as NKA and PACAP from 2-3·d.p.f. further support the theory that intrinsic enteric innervation is involved in the control of gut motility before the onset of exogenous feeding (Bisgrove et al, 1997;Holmberg et al, 2003;Holmberg et al, 2004;Holmberg et al, 2006;Holmqvist et al, 2004;Poon et al, 2003;Wallace et al, 2005).…”
Section: Introductionsupporting
confidence: 80%
“…and the expression of nitric oxide synthase (NOS), indicative of nitrergic neurons, as well as NKA and PACAP from 2-3·d.p.f. further support the theory that intrinsic enteric innervation is involved in the control of gut motility before the onset of exogenous feeding (Bisgrove et al, 1997;Holmberg et al, 2003;Holmberg et al, 2004;Holmberg et al, 2006;Holmqvist et al, 2004;Poon et al, 2003;Wallace et al, 2005).…”
Section: Introductionsupporting
confidence: 80%
“…*P<0.05. L-NAME, N G -nitro-L-arginine methyl ester; NO, nitric oxide; SNP, sodium nitroprusside Effects of NO in zebrafish larval intestine et al, 1998) and birds (Balaskas et al, 1995) as well as in amphibian (Holmberg et al, 2001) and teleost embryos and larvae (Villani, 1999;Poon et al, 2003;Holmqvist et al, 2004). The latter studies include zebrafish; however, the difference in time of appearance of NOS positive neurons between the middle-distal and proximal intestine observed in this study has not been reported previously.…”
Section: Discussionmentioning
confidence: 46%
“…A variety of neurotransmitters have been identified in the developing gut in mammals (Gintzler et al, 1980;Rothman and Gershon, 1982;Larsson et al, 1987;Timmermans et al, 1994;Brandt et al, 1996;van Ginneken et al, 1998), birds (Epstein et al, 1985;Rothman et al, 1986;Balaskas et al, 1995), amphibians (Holmberg et al, 2001;Maake et al, 2001;Badawy and Reinecke, 2003) and teleosts (Reinecke et al, 1997;Villani, 1999;Poon et al, 2003;Holmberg et al, 2004;Holmqvist et al, 2004;Pederzoli et al, 2004). In the zebrafish, enteric neurons are present in the gut before the onset of exogenous feeding (Raible et al, 1992;Bisgrove et al, 1997;Holmberg et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using in situ hybridization of zebrafish larvae revealed that by 55 h postfertilization all cell populations that express nNOS in the adult brain are present in zebrafish larvae (Holmqvist et al, 2000(Holmqvist et al, , 2004, indicating that NO is present during early development in the brain of zebrafish larvae. In both adults and larvae, information from peripheral chemoreceptors is sent to the CNS via afferent nerves in the nucleus tractus solitarius (NTS), where chemoreceptor information is integrated.…”
Section: Discussionmentioning
confidence: 99%